Crucial role of the protein C pathway in governing microvascular inflammation in inflammatory bowel disease - Scaldaferri, Franco; Sans, Miquel; Vetrano, Stefania; Graziani, Cristina; De Cristofaro, Raimondo; Gerlitz, Bruce; Repici, Alessandro; Arena, Vincenzo; Malesci, Alberto; Panes, Julian; Grinnell, Brian W.; Danese, Silvio (The Journal of clinical investigation, 2007)
Endothelial protein C receptor (EPCR) and thrombomodulin (TM) are expressed at high levels in the resting microvasculature and convert protein C (PC) into its activated form, which is a potent anticoagulant and antiinflammatory molecule. Here we provide evidence that in Crohn disease (CD) and ulcerative colitis (UC), the 2 major forms of inflammatory bowel disease (IBD), there was loss of expression of endothelial EPCR and TM, which in turns caused impairment of PC activation by the inflamed mucosal microvasculature. In isolated human intestinal endothelial cells, administration of recombinant activated PC had a potent antiinflammatory effect, as demonstrated by downregulated cytokine-dependent cell adhesion molecule expression and chemokine production as well as inhibited leukocyte adhesion. In vivo, administration of activated PC was therapeutically effective in ameliorating experimental colitis as evidenced by reduced weight loss, disease activity index, and histological colitis scores as well as inhibited leukocyte adhesion to the inflamed intestinal vessels. The results suggest that the PC pathway represents a new system crucially involved in governing intestinal homeostasis mediated by the mucosal microvasculature. Restoring the PC pathway may represent a new therapeutic approach to suppress intestinal inflammation in IBD.